Youth's perception towards the credibility of Harian Metro / Nor Raihan Abu Bakar, Norhayati Baba and Sharifah Yuliana Syed Ali Hanafiah - Abu Bakar, Nor Raihan; Baba, Norhayati; Syed Ali Hanafiah, Sharifah Yuliana (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2011)
The issue of credibility is a never-ending challenge for the media. Accuracy and reliability are elements that are of great importance to those interested in news from the available media. Credibility is also another key factor for a medium to be acceptable to its consumers. The core of credibility is trustfulness that shapes an audience’s confidence and identification toward a newspaper (Guo et. al, 2010). Some of the long-standing media credibility combine the concepts of believability, accuracy and depth of information to measure and confer credibility on news items. Hard news which focuses on significant events and major issues that influence existing policies are perceived more credible than soft news (Miller and Kurpius, 2010). As a tabloid-style newspaper, Harian Metro devotes much of it stories to soft news immensely laced with sensationalism and entertainment. Ehrlich, Flexner, Carruth & Hawkins (1980) defines tabloid as a newspaper (usually containing numerous pictures) printed on sheets that are half the size of larger newspaper and it is such a newspaper containing sensational news. Since Harian Metro is currently ranked first in newspaper readership in Malaysia, this has sparked questions on whether these criteria are considered by the public as credible. It is considered necessary to find out whether the public completely trust the tabloid. An investigation on whether the public rationalize the newspaper to pass judgments and decide to accept the content of the news items are crucial in understanding the perceived credibility of Harian Metro. The main objectives of this study are to identify youth’s perception towards source credibility and message credibility of the newspaper. In this study, we investigated the perceived credibility of youth readers of Harian Metro in terms of news articles and news sources through a survey in which questionnaire forms were distributed to readers aged between 20 to 40 years old, a segmentation of a society in any nation considered as the significant group in outlining the future of the country. This research clarifies an uncertain perception towards source and message credibility among the youth who reads Harian Metro.